2012
DOI: 10.4244/eijv8i3a57
|View full text |Cite
|
Sign up to set email alerts
|

Emergency extracorporeal membrane oxygenation in a hospital without on-site cardiac surgical facilities

Abstract: Extra-corporeal membrane oxygenation (ECMO) implantation is limited to specialized centres with cardiac surgery facilities. ECMO implantations in centres without on-site cardiovascular surgery facilities have been reported with ECMO system and surgeon dispatched from the referring hospital. We report the circumstances, feasibility, in-hospital complications and outcomes of ECMO implantation by an interventional cardiology team in a local hospital with a high-volume catheterization laboratory but without on-sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 24 publications
3
29
1
Order By: Relevance
“…Of note, however, patients with renal failure, as well as those that were centrally cannulated, two populations well-represented in our study, were excluded from analysis. Belle et al 12 described a similar cohort of 51 patients and reported only a 27.5% survival to discharge, likely due to the high percentage of patients cannulated in the setting of refractory cardiac arrest (47.1%). Flécher et al 13 recently published one of the largest series reporting outcomes of VA-ECMO for RCS with 260 patients.…”
Section: Discussionmentioning
confidence: 90%
“…Of note, however, patients with renal failure, as well as those that were centrally cannulated, two populations well-represented in our study, were excluded from analysis. Belle et al 12 described a similar cohort of 51 patients and reported only a 27.5% survival to discharge, likely due to the high percentage of patients cannulated in the setting of refractory cardiac arrest (47.1%). Flécher et al 13 recently published one of the largest series reporting outcomes of VA-ECMO for RCS with 260 patients.…”
Section: Discussionmentioning
confidence: 90%
“…While robust reporting of similar complication rates exists for ECPR used for IHCA or IHCA and OHCA combined [7,14,16,2325], less is available for comparison for strictly OHCA [6,8,9,11,12,15]. This robust reporting of international complication rates associated with ECPR following OHCA can provide centers wishing to monitor institutional complication rates a benchmark for comparison, and can guide decision making around risk-benefit decisions associated with this relatively complex and resource-intensive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in outcome between IHCA and OHCA results more from the duration of cardiac arrest than from the location of cardiac arrest itself (Tables 1-3) [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]. The difference in outcome between IHCA and OHCA results more from the duration of cardiac arrest than from the location of cardiac arrest itself (Tables 1-3) [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57].…”
Section: Extracorporeal Membrane Oxygenation For Out-of-hospital Cardmentioning
confidence: 99%